Determination of the incidence of sexually transmitted infections in pregnant women and puerperal adolescents at the erasmo meoz university hospital in the period 2024-2021 (Cuidado y Ocupación Humana, 2024)
STDs are a critical global public health problem. This study sought to determine the incidence of STDs in pregnant and postpartum adolescents admitted to the obstetrics and gynecology service of the Hospital Universitario Erasmo Meoz, a strategic place at regional and international level because it serves a large migrant population, which underscores the need for research and specific interventions. Methodology: This research uses a mixed approach to analyze the incidence of STD in pregnant and postpartum adolescents at the Hospital Universitario Erasmo Meoz. It integrates quantitative and qualitative data, examining demographic and diagnostic characteristics. The aim is to correlate variables such as infectious antecedents and time of diagnosis in order to improve STD management and prevention protocols. Results: At the Hospital Universitario Erasmo Meoz, a high incidence of STD was found in pregnant and postpartum adolescents who met the inclusion criteria, where the incidence had a significant deviation towards syphilis, followed by HIV and AIDS, diagnosed mainly during pregnancy. Conclusion: This study showed a high incidence of syphilis, HIV, AIDS and other STIs in a lower proportion in pregnant and puerperal adolescents, highlighting the need to implement diagnostic tests, management and prevention strategies in this age group.
Keywords: Sexually transmitted infections; adolescent; adolescent pregnancy